The effectiveness of humanoid diagram teaching strategy on care capacity and retention in novice nurses. (January 2022) - Tang, Yung-Hui; Chen, Hui-Ling; Chen, Hai-Yu; Chuang, Su-Wan; Liao, Li-Na; Huang, Li-Chi
Abstract: Aim: To examine the effectiveness of a Humanoid Diagram Teaching Strategy (HDTS) on care capabilities and retention of novice nurses. Background: Guiding novice nurses in clinical practice is a matter of concern and the use of diagrams in assisting the learning process and to promote learning efficiency has been acknowledged. Design: This is a quasi-experimental study with asynchronous repeated measurements for the experimental and control groups. Methods: The study was conducted in a medical centre in southern Taiwan with 24 novice nurses. The intervention, Humanoid Diagrams Teaching Strategy, contained three parts: the head and neck; trunk; and limbs. The HDTS was applied three time weekly. Each session lasted approximately 30 min and the training lasted 4 weeks. The effectiveness of HDTS was measured using Mini-CEX, CbD and retention rates in the 3rd and 6th months of novice nurses' experience. Results: After the HDTS, although increases in mini-CEX and CbD scores in the experimental group were greater than the control group, these differences were not statistically significant after considering the time interaction. But the 3rd month and 6th month novice nurses' retention rates were statistically significantly different by comparing the differences under the time interaction effects in both groups. Conclusions: The Humanoid Diagram Teaching Strategy is an effective tool for preceptors to use in assisting novice nurses in learning, improving their nursing care knowledge and technical skills and to increase their retention rate.